IMPLEMENTASI METODE TALAQQI DALAM MENINGKATKAN KUALITAS HAFALAN HADIS ARBA’IN AN-NAWAWI SANTRI KELAS IX DI PONDOK PESANTREN BIN BAZ 4 WANGON - Fauzan Ananta Fahmi; Muhammad Riziq Firdaus; Ida Bagus Afif Ratrian Sadewa Wijaya; Nurul Hidayat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The talaqqi method is one of the instructional strategies implemented at Bin Baz 4 Wangon Islamic Boarding School. This method is applied in the teaching of Hadith Arba’in An-Nawawi, one of the core subjects for ninth-grade students. The main objective of this study is to examine the implementation of the talaqqi method in improving students’ memorization quality of Hadith Arba’in An-Nawawi. The research employs a descriptive approach that integrates both qualitative and quantitative data. Data were collected through classroom observations, interviews with teachers and students, memorization tests, and questionnaires distributed to ninth-grade students. The study involved 14 students as participants. The observation results revealed that the talaqqi method helped students focus more on accurate recitation and pronunciation during their memorization sessions. Based on the memorization test results, the average mastery rate reached 85%, categorized as good. Furthermore, 89% of students responded positively in the questionnaire, stating that this method facilitated their understanding and memorization of the hadith. The findings indicate that the talaqqi method is an effective pedagogical approach for enhancing students’ memorization abilities of Hadith Arba’in An-Nawawi. It not only improves accuracy and fluency in recitation but also fosters greater motivation and enthusiasm for learning among students.